INTRAVENOUS THERAPY IN HOSPITALIZED OLDER ADULTS: CARE EVALUATION - Ana Cláudia Roman Rós; Daniela Ramos Oliveira; Raquel Debon; Maira Scaratti (Universidade Federal do Paraná, 2017)
The aim of this study was to evaluate the nursing care related to peripheral intravenous therapy in older adults hospitalized or under observation in a teaching hospital in southern Brazil, between August and September 2016. This prospective quantitative study evaluated intravenous therapy infection prevention measures, by means of an instrument based on the recommendations of the Brazilian Health Regulatory Agency. The study included 80 patients with a mean age of 70.7 years, 51 (63.7%) of whom were male. The identification was adequate in 15 (18.8%) of the venous accesses and the correct completion of the labels was not identified for any solution evaluated. The dressing for catheter fastening was unclean in 29 (36.3%) cases and the incidence of phlebitis occurred in six (7.5%) patients. It was concluded that there are nonconformities, which impact on the safety of the hospitalized patient, requiring monitoring of the quality of care and ongoing education of the professionals.